2017
DOI: 10.1049/iet-epa.2016.0270
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of a novel clutch system for in‐wheel motor drive electric vehicles

Abstract: In-wheel motor drive electric vehicles mainly adopt fastening connection between hub and motor, so the electromagnetic impact and the mechanical impact are inevitable. The electromagnetic impact endangers the battery and the control system and the mechanical impact brings bad driving experience. Newly designed bistable electromagnetic clutches are embedded into the hub motor to realise flexible connection and avoid the impact. The goal of this study is to analyse the dynamic movement process of the clutch in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Similarly, Xu et al proposed the use of an electromagnetic disconnect friction clutch in P2 architecture to enhance both riding comfort and engine start time in a variety of situations [7]. Huang et al demonstrated that EDCs may also be utilized in automotive powertrains, where they can be used as a flexible link between the wheel hub and motor for high levels of comfort and smooth power transmission [8,9]. A fractional electromagnetic compound disk brake is another application of electromagnetic actuators, and it demonstrates favorable braking performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Xu et al proposed the use of an electromagnetic disconnect friction clutch in P2 architecture to enhance both riding comfort and engine start time in a variety of situations [7]. Huang et al demonstrated that EDCs may also be utilized in automotive powertrains, where they can be used as a flexible link between the wheel hub and motor for high levels of comfort and smooth power transmission [8,9]. A fractional electromagnetic compound disk brake is another application of electromagnetic actuators, and it demonstrates favorable braking performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Torque and speed controllers are controlled based on Direct Torque Control (DTC) and Field-Oriented Control (FOC). These controllers are designed using linear and nonlinear control methods such as PI, LQR, dead beat, sliding mode, flatness, fuzzy [10][11][12][13][14], or hybrid controllers such as fuzzy-neural, fuzzy-sliding, and PIfuzzy [14][15][16][17]. However, the torque response has a slight pulsation, and the actual speed response quickly and accurately tracks the required speed [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Torque and speed controllers are controlled based on direct torque control (DTC) and based on field-oriented control (FOC). In addition, these controllers are designed by linear and nonlinear control methods such as PI, LQR, Dead 2 beat, sliding control, flatness, fuzzy, [10][11][12][13] or hybrid controller such as fuzzy-neural, fuzzy-sliding mode control [14][15][16][17]. This research results only stop to evaluate the effectiveness of each solution for torque and speed control in the case of AFPMSM motors operating with unchanged load torque or motor parameters.…”
Section: Introductionmentioning
confidence: 99%